A new measure of entropy of continuous random variable. (1st October 2016) - Al-Omari, Amer Ibrahim
ABSTRACT: A new estimator of entropy of continuous random variable is suggested in this article. The newly suggested estimator is a modified version of Ebrahimi et al. entropy estimator. This estimator is compared with its counterparts suggested by Vasicek, Ebrahimi et al., and Al-Omari in terms of root mean squared errors and bias values. The consistency of the estimator is proved, and some of its properties are provided. The suggested estimator is found to be more efficient than its competitors.